Outcome beyond third-line chemotherapy for metastatic triple-negative breast cancer in the French ESME program. (April 2021) - Cabel, Luc; Carton, Matthieu; Pistilli, Barbara; Dalenc, Florence; Vanlemnens, Laurence; Levy, Christelle; Jacot, William; Debled, Michel; Loeb, Agnes; Hennequin, Audrey; De la Motte Rouge, Thibault; Laborde, Lilian; et al.
Abstract: Purpose: Among metastatic breast cancer (MBC) patients, those with a triple-negative breast cancer phenotype (mTNBC) have the worst prognosis, but the benefit of chemotherapy beyond second line on outcome remains uncertain. The purpose of this study was to identify predictive factors of outcome after third- or fourth-line chemotherapy. Methods: The ESME-MBC database is a French prospective real-life cohort with homogeneous data collection, including patients who initiated first-line treatment for MBC (2008–2016) in 18 cancer centers. After selection of mTNBC cases, we searched for independent predictive factors (Cox proportional-hazards regression models) for overall survival (OS) on third- and fourth-line chemotherapy (OS3, OS4). We built prognostic nomograms based on the main prognostic factors identified. Results: Of the 22, 266 MBC cases in the ESME cohort, 2903 were mTNBC, 1074 (37%) and 598 (20%) of which had received at least 3 or 4 lines of chemotherapy. PFS after first- and second-line chemotherapy (PFS1, PFS2) and number of metastatic sites ≥3 at baseline were identified by multivariate analysis as prognostic factors for both OS3 (HR = 0.76 95%CI[0.66–0.88], HR = 0.55 95%CI[0.46–0.65], HR = 1.36 95%CI[1.14–1.62], respectively), and OS4 (HR = 0.76 95%CI[0.63–0.91], HR = 0.56 95%CI[0.45–0.7], HR = 1.37 95%CI[1.07–1.74]), respectively. In addition, metastasis-free interval was identified as a prognostic factor for OS3 (p = 0.01), while PFS3 influenced OS4 (HR = 0.75 95%CI[0.57–0.98]). Nomograms predicting OS3 and OS4 achieved a C-index of 0.62 and 0.61, respectively. Conclusion: The duration of each previous PFS is a major prognostic factor for OS in mTNBC patients receiving third- or fourth-line chemotherapy. The clinical utility of nomograms including this information was not demonstrated. Highlights: After 3rd- or 4th-line therapy, PFS remained linear in the majority of women with metastatic triple-negative breast cancer. The duration of each previous PFS had an impact on the OS associated with subsequent lines. PFS2 was more strongly predictive of outcome than PFS1 for third-line therapy. PFS2 and PFS3 had an impact on outcome irrespective of PFS1 for fourth-line therapy. The clinical utility of nomograms including duration of each previous PFS to predict OS was not sufficient.